Structural properties of nanocomposite SiO₂(Si) films obtained by ion-plasma sputtering and thermal annealing - Bratus, O.L.; Evtukh, A.A.; Lytvyn, O.S.; Voitovych, M.V.; Yukhymchuk, V.О. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
The nanocomposite SiO₂(Si) films containing Si nanoclusters inside insulating SiO₂matrix are promising for many nanoelectronics applications. The ion-plasma sputtering of Si in O₂ containing gas mixture and following thermal annealing have been used to form nanocomposite SiO₂(Si) films. The structural properties of the obtained films have been studied using several methods. Among them, there were ellipsometry, IR spectroscopy, Raman spectroscopy, and AFM. Transition of SiOx matrix into insulating SiO₂ matrix has been revealed by IR spectroscopy. The shift of the transmittance spectra toward high frequency region and the increase in their intensity have been observed. The existence of amorphous and nanocrystalline phases into SiO₂(Si) films have been confirmed using Raman spectroscopy. Two material phases on the film surface, namely SiO₂ and Si, and surface density of silicon nanoclusters have been determined using AFM. It was shown that the size of silicon nanoclusters and their surface density depend on the level of enrichment with silicon of the initial SiOx film after ion-plasma sputtering and the temperature of subsequent annealing.